Pembentukan Portofolio Optimal Model Markowitz Menggunakan Metode Sharpe (Studi Kasus Pada Saham Jakarta Islamic Index) - Fiona Melta; Dewi Murni (Journal of Mathematics UNP, 2021)
Investment is the  activity of placing  funds or money  with the  aim of  making a  profit.  In addition to profits, investments also have risks that can be minimized by forming an optimal portfolio using the Markowitz Model. The purpose of this study is to determine the combination and weight of funds  from  each  stock  that  makes  up  the  optimal  portfolio  and  to  determine  the  optimal  expected return and risk of the Markowitz model based on the Sharpe Ratio. This study uses stock data of the Jakarta  Islamic  Index  during  the  period  August –November  2020. The  results  of  the  analysis  of  30 stocks of the Jakarta Islamic Index obtained 5 stocks forming an optimal portfolio with fund weights for  each  share,  namely  CTRA  5.32%,  INCO  40.78%,  SCMA  2.97%,  SMGR  0.23%.  ,  and  TPIA 50.7%  with  expected  return,  portfolio  risk  and  maximum  sharpe  ratio  of  0.3760021%,  0.010933%, and 0.359600991, respectively.